2021
DOI: 10.3390/cells10081915
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Enhances Angiogenesis-Related Gene Responses in Skeletal Muscle of Patients with Chronic Heart Failure

Abstract: Peripheral myopathy consists of a hallmark of heart failure (HF). Exercise enhanced skeletal muscle angiogenesis, and thus, it can be further beneficial towards the HF-induced myopathy. However, there is limited evidence regarding the exercise type that elicits optimum angiogenic responses of skeletal muscle in HF patients. This study aimed to (a) compare the effects of a high-intensity-interval-training (HIIT) or combined HIIT with strength training (COM) exercise protocol on the expression of angiogenesis-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…In addition, fold changes in the intramuscular IL-8 expression were positively correlated with the improvement of exercise capacity in these patients, potentially implying a beneficial role of exercise traininginduced local inflammation, as part of an on-going remodeling process in the exercising muscles. Combining these observations with the induction of skeletal muscle hypertrophy [24] and angiogenesis [30] that we have previously reported in these particular groups of HF patients following the same exercise training protocols, we might assume that an intramuscular inflammation program may be associated with muscle remodeling and adaptations to exercise training.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, fold changes in the intramuscular IL-8 expression were positively correlated with the improvement of exercise capacity in these patients, potentially implying a beneficial role of exercise traininginduced local inflammation, as part of an on-going remodeling process in the exercising muscles. Combining these observations with the induction of skeletal muscle hypertrophy [24] and angiogenesis [30] that we have previously reported in these particular groups of HF patients following the same exercise training protocols, we might assume that an intramuscular inflammation program may be associated with muscle remodeling and adaptations to exercise training.…”
Section: Discussionsupporting
confidence: 62%
“… 281 , 282 Several studies have revealed that both endurance and resistance exercise increase the expression of VEGF in the brain, heart, skeletal muscle, and bones. 95 , 283 , 284 HIIT training contributed to an overall increase in the expression levels of VEGF and VEGF receptor-2 (VEGFR2) in skeletal muscle of subjects with peripheral myopathy associated with heart failure, promoting muscle capillarization, 285 and differentially expressed genes of the skeletal muscle showed the PI3K/Akt signaling pathway was activated in response to HIIT. 286 Of note, it has been found that the PI3K/Akt axis is not only activated by a range of exerkines mentioned above, but also in response to mechanical stress.…”
Section: Molecular Mechanisms Of Tissue Regeneration Induced By Exercisementioning
confidence: 99%
“…The effect and symptoms of CHF on individuals' everyday routines are reflected in their health-related quality of life (QoL), which is usually decreased in these patients [17,18]. During the last decades, studies investigating aerobic exercise are shown to improve microcirculation [19,20] and vascular endothelial function [21][22][23], exercise capacity [21][22][23][24][25][26], skeletal myopathy [19,27,28], and QoL [25,29,30] in CHF patients. The most recent 2021 European guidelines for managing and treating chronic heart failure, include a class IA recommendation for patients with CHF to engage in regular aerobic exercise protocols which are the most studied aspects of cardiac rehabilitation (CR) pro- grams [31].…”
Section: Introductionmentioning
confidence: 99%